2010
DOI: 10.1080/10510970903396477
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relationship Between Perceived Message Sensation Value and Perceived Message Effectiveness: Analysis of PSAs From an Effective Campaign

Abstract: The current study is an analysis of public service announcements (PSAs) from an effective safer sex campaign that utilized a sensation-seeking targeting (SENTAR) approach. Two random samples of heterosexually active young adults (sample one N = 1,463, sample two N = 895) viewed different sets of safer sex PSAs on a laptop computer and answered questions about their perceived sensation value and perceived effectiveness. Multiple regression analyses examined the impact of (a) demographic, (b) individual differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…An interpretation of effectiveness perceptions in terms of perceived persuasiveness is common (e.g., Kang & Cappella, 2008; Niederdeppe, Farrelly, Nonnemaker, Davis, & Wagner, 2011; Noar, Palmgreen, Zimmerman, Lustria, & Lu, 2010). After all, persuasion scholarship focuses on how messages might move audiences from one position to another, which at the very least seems relevant to understanding how effective a message is perceived to be.…”
Section: Foundations Of Perceived Message Effectiveness Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…An interpretation of effectiveness perceptions in terms of perceived persuasiveness is common (e.g., Kang & Cappella, 2008; Niederdeppe, Farrelly, Nonnemaker, Davis, & Wagner, 2011; Noar, Palmgreen, Zimmerman, Lustria, & Lu, 2010). After all, persuasion scholarship focuses on how messages might move audiences from one position to another, which at the very least seems relevant to understanding how effective a message is perceived to be.…”
Section: Foundations Of Perceived Message Effectiveness Researchmentioning
confidence: 99%
“…This may not be an issue if these different measures in some way all measure PE. For example, Noar et al (2010) observed that their measures of cognitive and affective reactions, personal utility, and PE correlated with each other, raising the possibility that there may be an underlying dimension related to “positive feelings” toward a given PSA. For example, it is possible that perceived effectiveness itself is a broad dimension that could be better assessed through a multiple item scale including items assessing cognitive reaction, emotional reaction, and personal utility, among others.…”
Section: Existing Pe Measures: Threats To Construct Validitymentioning
confidence: 99%
“…Messages high in sensation value elevate arousal or stimulation due to being dramatic, exciting, and novel (Morgan, Palmgreen, Stephenson, Lorch, & Hoyle, 2003). Similarly, PMSV refers to an individual's perception of high-sensation-value qualities within an ad along three dimensions (Noar, Palmgreen, Zimmerman, Lustria, & Lu, 2010;Palmgreen, Stephenson, Everett, Baseheart, & Francies, 2002): dramatic impact (e.g., graphicness), emotional arousal (e.g., excitement), and novelty (e.g., uniqueness). Stephenson and colleagues (Stephenson, 2003;Stephenson & Palmgreen, 2001) argue that PMSV enhances message persuasiveness by appealing to an individual's psychobiological needs of activation.…”
Section: Downloaded By [Ryerson University] At 10:23 01 December 2014mentioning
confidence: 99%
“…In particular, the PSA Translation was able to use humor in a way to “lighten” up a serious subject (AIDS/STDs) and to promote conversation on that topic. Given that our large-scale quantitative data suggest that this PSA was relatively effective (second only to My Story; Noar et al, 2010), humor in this case may have been well used. On the other hand, for example, humor used to make fun of the Boyfriend PSA that focused on the “extreme sports” component of the ad, rather than its safer sex persuasive message, is unlikely to have engendered the desired outcome.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, our large-scale survey data indicated that of the 5 PSAs used in the campaigns, the PSAs viewed as most effective were Translation and My Story (Noar, Palmgreen, Zimmerman, Lustria, & Lu, 2010). In the current data, the PSA that sparked the most conversation among romantic partners (boyfriend or girlfriend) was My Story (53%), closely followed by Boyfriend (47%).…”
Section: Resultsmentioning
confidence: 94%